2020
DOI: 10.1111/tid.13353
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of COVID‐19 in liver transplant recipients: A preliminary report from Northwestern Italy

Abstract: Covid-19 pandemic is deeply affecting transplant activity worldwide. It is unclear whether solid organ transplant recipients are at increased risk of developing severe complications and how they should be managed, also concerning immunosuppression. This is a report about the course and management of SARS-CoV-2 infection in liver transplant recipients from a single center in Northwestern Italy in the period March-April 2020. Three patients who were treated at our institution are reported in detail, whereas summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 13 publications
(25 reference statements)
1
26
0
1
Order By: Relevance
“…Notably, in this large case series the mortality rate was higher among patients with a follow‐up ≥2 years from LT 19 . This trend is confirmed by other reports, 4,18 but the underlying reasons remain unclear. One potential explanation could be the longer exposure to IS therapy, a known risk factor for developing IS‐related complications such as hypertension or diabetes that might play a role in increasing the mortality risk for COVID‐19.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Notably, in this large case series the mortality rate was higher among patients with a follow‐up ≥2 years from LT 19 . This trend is confirmed by other reports, 4,18 but the underlying reasons remain unclear. One potential explanation could be the longer exposure to IS therapy, a known risk factor for developing IS‐related complications such as hypertension or diabetes that might play a role in increasing the mortality risk for COVID‐19.…”
Section: Resultssupporting
confidence: 85%
“…As of June 10, 2020, there are 244 reported cases of LT infected by COVID‐19, 3‐21 including 240 adult and 4 pediatric LT recipients (Table 1). So far, the available data are scarce, not homogeneous, and based mainly on case reports, correspondences, and letters to the editors; thus, the analysis and the interpretation of data must be cautious.…”
Section: Resultsmentioning
confidence: 99%
“…To be included, the study must have reported clinical data on adult (A-CA) or pediatric (P-CA) cancer patients and SOT or HCT recipients with confirmed COVID-19. Our inclusion and exclusion criteria identified 64 SOT studies, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 11 HCT studies,…”
Section: Methodsmentioning
confidence: 99%
“…[62][63][64] En los pacientes con manifestaciones menores, se recomienda continuar con el esquema de inmunosupresión habitual. 67 1 63.0 10.0 0 0.0 0.0 Zhong et al 68 1 37.0 9 días 0 0.0 0.0 Tschopp et al 69 5 56.0 47 meses ND 0.0 0.0 Gao et al 70 73 1 80.0 14.2 ND 0.0 0.0 Müller et al 74 1 55.0 1.0 100 0.0 0.0 Yi et al 75 3 54.8 5.5 90 33.3 0.0 Modi et al 76 1 32.0 7.0 100 0.0 0.0 Patrono et al 77 10 65.6 7.0 ND 20 10 Massoumi et al 44 5 48.6 42.2 días ND 0.0 0.0 Massoumi et al 44 9 ND ND ND 33.3 0.0 Belli et al 78 103 65.0 ND > 56 37 16 ND = no disponible. * Promedio en series de caso.…”
Section: Infección Por Covid-19/sars-cov-2 En Receptores De Trasplantunclassified